Synthesis and Biological Evaluation of a New Structural Simplified Analogue of cADPR, a Calcium-Mobilizing Secondary Messenger Firstly Isolated from Sea Urchin Eggs - Stefano D’Errico; Nicola Borbone; Bruno Catalanotti; Agnese Secondo; Tiziana Petrozziello; Ilaria Piccialli; Anna Pannaccione; Valeria Costantino; Luciano Mayol; Gennaro Piccialli; Giorgia Oliviero (Marine Drugs, 2018)
Herein, we reported on the synthesis of cpIPP, which is a new structurally-reduced analogue of cyclic ADP-ribose (cADPR), a potent Ca2+-releasing secondary messenger that was firstly isolated from sea urchin eggs extracts. To obtain cpIPP the “northern” ribose of cADPR was replaced by a pentyl chain and the pyrophosphate moiety by a phophono-phosphate anhydride. The effect of the presence of the new phosphono-phosphate bridge on the intracellular Ca2+ release induced by cpIPP was assessed in PC12 neuronal cells in comparison with the effect of the pyrophosphate bridge of the structurally related cyclic N1-butylinosine diphosphate analogue (cbIDP), which was previously synthesized in our laboratories, and with that of the linear precursor of cpIPP, which, unexpectedly, revealed to be the only one provided with Ca2+ release properties.